Analysis of gender discourse bias and gender discrimination in social media: a case study of the TikTok platform - Yin, Qingxia; Binti Abdullah, Karmilah (Immigrant Institutet, 2024)
In the contemporary landscape of new media, social media platforms, particularly exemplified by TikTok, offer female users accessible and cost-effective means for self-expression and communication. However, this study reveals that such platforms, despite their apparent openness and liberality, have not effectively challenged or changed the persistent and deep-rooted issue of gender discrimination that women face. This research adopts a qualitative content analysis and specifically focuses on the TikTok platform, where female users frequently encounter various forms of gender discourse bias and discrimination. The findings suggest that female users on TikTok often face stigmatization through the internet lexicon and the commodification of physical appearance, reflecting broader societal issues of gender inequality and objectification. Simultaneously, a segment of the female user base on TikTok is actively engaging in challenging and negotiating these entrenched stereotypes, striving to redefine their representation in the digital space. Furthermore, the research highlights how the anonymity of the internet, the media’s role in encoding and perpetuating gender stereotypes, and the consumerist traps set by capitalist market dynamics, collectively contribute to an illusory facade of gender equality. This facade obscures the underlying realities of discourse bias and gender discrimination that persist in the digital realm.